The legal nature Contracts of building، operating and distribution of petroleum products in Iraq- Analytical study - شبيب, كاظم مطشر شبيب (Journal of Petroleum Research and Studies, 2020)
Contracts of building، operating and petroleum products that are held with companies and individual are among the important contracts at present. The importance of these contracts comes from the importance of its products because they are linked to the lifes of citizens either for direct consumption or for industrial and commercial purposes for the continuation of daily life. These contracts have an impact on the reality of the economic development of the state because of its economy، projects and services are linked to the petroleum products. Of course، their association with companies and individuals through the services they provide has led to the emergence of legal issues and problems that need legal coverage and treatment. The issue of the legal adaptation of Contracts of building، operating and petroleum products is one of the important issues in the legal field because determining the nature of the legal relationship and its return to a particular legal system is essential subject to determine the legal rules that gover it and to know the applicable law. Especially that the contract - the subject of research - is one of the rare contracts، which were not given much attention by researchers so this is one of the reasons that led us to research the legal nature of petroleum products contracts that are held with companies and individuals by surrounding their characteristics and lega adaptation.